Polarization Mode Dispersion - Galtarossa, Andrea; Menyuk, Curtis R.; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
This book contains a series of tutorial essays on polarization mode dispersion (PMD) by the leading experts in the field. It starts with an introductory review of the basic concepts and continues with more advanced topics, including a thorough review of PMD mitigation techniques. Topics covered include mathematical representation of PMD, how to properly model PMD in numerical simulations, how to accurately measure PMD and other related polarization effects, and how to infer fiber properties from polarization measurements. It includes discussions of other polarization effects such as polarization-dependent loss and the interaction of PMD with fiber nonlinearity. It additionally covers systems issues like the impact of PMD on wavelength division multiplexed systems. This book is intended for research scientists or engineers who wish to become familiar with PMD and its system impacts.
to polarization mode dispersion in optical systems -- Modelling of polarization mode dispersion in optical communications systems -- Statistical properties of polarization mode dispersion -- Three Representations of Polarization Mode Dispersion -- The inverse PMD problem -- Numerical modeling of PMD -- Applications of importance sampling to polarization mode dispersion -- PMD & PDL -- Interaction of nonlinearity and polarization mode dispersion -- PMD measurement techniques and how to avoid the pitfalls -- PMD measurements on installed fibers and polarization sensitive components -- Reflectometric measurements of polarization properties in optical-fiber links -- PMD impact on optical systems: Single- and multichannel effects -- Polarization effects and performance of fiber optic recirculating loops -- PMD compensation techniques -- Low-PMD spun fibers -- PMD emulation.
Keywords: Physics; Optics; Optoelectronics; Plasmons (Physics).; Electrical engineering; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Communications Engineering, Networks; Electronic books